Polycyclic Aromatic Hydrocarbons: Sources, Toxicity, and Remediation Approaches - Patel, Avani Bharatkumar; Shaikh, Shabnam; Jain, Kunal R.; Desai, Chirayu; Madamwar, Datta (Frontiers in microbiology, 2020)
Polycyclic aromatic hydrocarbons (PAHs) are widespread across the globe mainly due to long-term anthropogenic sources of pollution. The inherent properties of PAHs such as heterocyclic aromatic ring structures, hydrophobicity, and thermostability have made them recalcitrant and highly persistent in the environment. PAH pollutants have been determined to be highly toxic, mutagenic, carcinogenic, teratogenic, and immunotoxicogenic to various life forms. Therefore, this review discusses the primary sources of PAH emissions, exposure routes, and toxic effects on humans, in particular. This review briefly summarizes the physical and chemical PAH remediation approaches such as membrane filtration, soil washing, adsorption, electrokinetic, thermal, oxidation, and photocatalytic treatments. This review provides a detailed systematic compilation of the eco-friendly biological treatment solutions for remediation of PAHs such as microbial remediation approaches using bacteria, archaea, fungi, algae, and co-cultures. In situ and ex situ biological treatments such as land farming, biostimulation, bioaugmentation, phytoremediation, bioreactor, and vermiremediation approaches are discussed in detail, and a summary of the factors affecting and limiting PAH bioremediation is also discussed. An overview of emerging technologies employing multi-process combinatorial treatment approaches is given, and newer concepts on generation of value-added by-products during PAH remediation are highlighted in this review.Polycyclic aromatic hydrocarbons (PAHs) are widespread across the globe mainly due to long-term anthropogenic sources of pollution. The inherent properties of PAHs such as heterocyclic aromatic ring structures, hydrophobicity, and thermostability have made them recalcitrant and highly persistent in the environment. PAH pollutants have been determined to be highly toxic, mutagenic, carcinogenic, teratogenic, and immunotoxicogenic to various life forms. Therefore, this review discusses the primary sources of PAH emissions, exposure routes, and toxic effects on humans, in particular. This review briefly summarizes the physical and chemical PAH remediation approaches such as membrane filtration, soil washing, adsorption, electrokinetic, thermal, oxidation, and photocatalytic treatments. This review provides a detailed systematic compilation of the eco-friendly biological treatment solutions for remediation of PAHs such as microbial remediation approaches using bacteria, archaea, fungi, algae, and co-cultures. In situ and ex situ biological treatments such as land farming, biostimulation, bioaugmentation, phytoremediation, bioreactor, and vermiremediation approaches are discussed in detail, and a summary of the factors affecting and limiting PAH bioremediation is also discussed. An overview of emerging technologies employing multi-process combinatorial treatment approaches is given, and newer concepts on generation of value-added by-products during PAH remediation are highlighted in this review.